The state of the art on hypodermoclysis in child health care: scoping review - Isabella Pavarine de Souza; Maria Paula Custódio Silva; Ana Letícia Ribeiro Oliveira; Giselle Vieira de Souza; Jesislei Bonolo do Amaral Rocha; Divanice Contim (Rev Rene)
Objective: to mapping the evidence on hypodermoclysis in child health care. Methods: this is a scope review, with a search in Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Health Sciences Literature, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, Scopus Elsevier, Web of Science and Embase. Studies published in Portuguese, English and Spanish were included, with no time cut. Results: a total of 11 studies were analyzed, with a predominance of literature reviews. The main themes were: use of recombinant human hyaluronidase as a facilitator of subcutaneous absorption; comparison between subcutaneous and intravenous rehydration; advantages of hypodermoclysis; patient pain and puncture attempts. Conclusion: this study allowed mapping the scientific evidence on hypodermoclysis, revealing it to be a viable and valid alternative for administering medications in children. Contributions to practice: the use of the technique can bring benefits and provides evidence to indicate and apply it in child care.